2008
DOI: 10.2134/agronj2007.0352
|View full text |Cite
|
Sign up to set email alerts
|

Growth Analysis of Faba Bean and Lupin with Volunteer Barley Competition in a Northern Environment

Abstract: A gronomy J our n al • Volu me 10 0 , I s sue 4 • 2 0 0 8 electronic or mechanical, including photocopying, recording, or any information storage and retrieval system, without permission in writing from the publisher. N arrow-leafed lupin and tannin-free faba bean are new pulse crops for the Parkland region of Alberta, Canada. Since 2002, tannin-free faba bean production has increased due to its high yield, high protein, high energy, a reduction in antinutritional factors (e.g., tannin), and similar production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…(1993). Also in white lupin Strydhorst et al. (2008) reported that the amount of light available at the top of the canopy was reduced proportionately by about 0·50 in the presence of barley.…”
Section: Discussionsupporting
confidence: 80%
“…(1993). Also in white lupin Strydhorst et al. (2008) reported that the amount of light available at the top of the canopy was reduced proportionately by about 0·50 in the presence of barley.…”
Section: Discussionsupporting
confidence: 80%
“…The aggressiveness of the Fusarium isolates was initially assessed on the two L. angustifolius cultivars registered in Canada, 'Arabella' and 'Rose', which have been studied extensively in Alberta (Blade et al, 2004;Canadian Food Inspection Agency, 2005Strydhorst et al, 2008aStrydhorst et al, , 2008bStrydhorst et al, , 2008c. Inoculum was produced by homogenizing 13-to 15-day-old Fusarium cultures grown on PDA in 60 mL of sdH 2 O.…”
Section: Aggressivenessmentioning
confidence: 99%